Gaining Access to International Investment Agreements’ Protections through the Structuring or Restructuring of Investments : The Colombian Case - How can Investors Protect their Investments in Colombia through the Practice of Treaty Shopping? (2023)
This thesis explores the realm of international investment agreements and their potential to safeguard investments through the strategic corporate structuring or restructuring of investments, harnessing the benefits contained in international investment agreements. The initial focus is on the fundamental role of these international instruments in ensuring the security of foreign investments. As the global investment landscape undergoes transformations, the thesis underscores the adaptive strategies investors employ to navigate the evolving legal framework. The concept of treaty shopping is explored as a strategic tool embraced by investors to optimize protective measures. The motivations and perceptions across stakeholders, including governments, investors, and judicial bodies, is analyzed in the first sections of the thesis. The study then examines the different limitations within the treaty shopping practice. Jurisdictional constraints, encompassing ratione personae, ratione materiae, and ratione temporis, are studied. The thesis further analyzes normative bounds, encompassing elements like denial of benefits clauses, and, lastly, it discusses the concept of the abuse of rights doctrine as an additional limit to the treaty shopping practice. Shifting attention to Colombia, the thesis examines the nation's array of international investment agreements, evaluating their approach to the concept of treaty shopping. Real-world disputes involving these strategies, where Colombia has been implicated, are also analyzed. Concluding, actionable recommendations are proposed for investors navigating Colombia's evolving investment landscape and recent political uncertainty. Bridging theory and practical scenarios, the thesis offers insights for investors and legal practitioners engaging with international investment protections within Colombia. In essence, this thesis constructs a strategic guide, customized to Colombia's dynamic political landscape, aiding investors in effectively utilizing international investment agreements for investment security. The Colombian context serves as a distinct backdrop, illustrating the interplay between treaty provisions and adaptive investment protection strategies amid the global economic landscape.